Synergistic Effect of Rubus crataegifolius and Ulmus macrocarpa Against Helicobacter pylori Clinical Isolates and Gastritis - Park, Jung Uoon; Cho, Jin Sook; Kim, Jong Seok; Kim, Hyun Kyu; Jo, Young Hee; Rahman, Md Aziz Abdur; Lee, Young Ik (Frontiers in Pharmacology, 2020)
Helicobacter pylori is one of the most widespread infections involved in the pathogenesis of chronic gastritis, peptic ulcer and gastric cancer. Hence, there is an urgent need to develop medications against H. pylori. This study aimed to evaluate synergistic effect of Rubus crataegifolius (RF) and Ulmus macrocarpa Hance (UL) against H. pylori. Antibacterial susceptibility of each extract either separately or in combination were studied against two H. pylori standard strains and eleven clinical isolates using agar dilution method. The effect of the extracts on H. pylori inoculated Balb/c mice model was also studied using single dosing (100 mg/kg each) approach. The MIC50 of RF and UL were more than 100 and 200 µg/mL, respectively against the tested strains. However, simultaneous treatment with RF and UL at 75 and 50 µg/mL, respectively, showed decreased viable cell number, MIC70, and at 75 µg/mL each showed synergic effect with MIC90. On H. pylori inoculated Balb/c mice model, RF and UL separately (100 mg/kg each) showed moderate anti-H. pylori effect, while simultaneous treatment of RF and UL with same dose showed significant synergistic anti-gastric effects in stomach. The results showed a significant synergistic effect of plants extract against H. pylori infection and eventually gastric mucosal damage. Our finding could be considered a valuable support in the treatment of H. pylori induced gastritis and may contribute to the development of new and safe combined herbal product as anti-H. pylori regimens.